Is the Anthropic Principle Possible as a Theological Argument? - Tsekov, Tsvetin (Forum Theologicum Sardicense, 2025)
The present research delves into a discussion with Christos Yannaras and George Dragas on the so-called “Anthropic Principle” in modern Orthodox theology. The author concludes that anthropocentrism in a theological context is not a proper methodological approach.